INDENTIFIKASI JENIS PENYAKIT DAN GANGGUAN KESEHATAN KARANG HIAS Acropora sp. HASIL TRANSPLANTASI PT. LOMBOK SAMUDERA ABADI DI PESISIR PANTAI MUTIARA KABUPATEN SUMBAWA - Muhammad Fajri; Anita Prihatini Ilyas; Zainul Arifin (Program Studi Ilmu Perikanan, Fakultas Ilmu dan Teknologi Hayati, Universitas Teknologi Sumbawa, 2025)
Coral diseases and health disorders are among the primary factors threatening the survival and sustainability of coral reef ecosystems. Coastal areas, particularly those adjacent to human settlements, are highly vulnerable to environmental pressures arising from both natural and anthropogenic factors. One such area is the coastal waters of Pantai Mutiara, Pulau Kaung Village. This study aims to identify the types of coral diseases and health disorders present in the area and to assess the environmental factors influencing their occurrence. The research was conducted from April to May 2025 in the coastal waters of Pantai Mutiara. Data collected included the types of coral diseases and health disorders, as well as water quality parameters. Field observations were carried out through direct documentation of infected corals, which were subsequently identified using the Underwater Cards for Assessing Coral Health on Indo-Pacific Reefs. The results revealed several coral diseases and health disorders, namely White Syndrome, Bleaching, Algal Competition, and Sediment Damage. These conditions are presumed to be associated with both anthropogenic activities and natural environmental factors. The highest overall prevalence was recorded at a depth of 4 meters, reaching 25%. Bleaching was most frequently observed at a depth of 2 meters, affecting three coral colonies. According to the Indonesian Government Regulation No. 22 of 2021, the water quality in the study area remains within acceptable standards, indicating that the environmental condition is still adequate to support coral growth and survival. Keywords: Prevalence, Diseases, Health Disorders, Coral, Pearl Beach Waters.